2002
DOI: 10.1007/s00261-001-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyolipoma of the liver with least amount of fat component: imaging features of CT, MR, and angiography

Abstract: We report two cases of angiomyolipoma of the liver, where small amounts of fat on computed tomography, magnetic resonance imaging, and angiography made distinguishing this tumor from other hypervascular tumors difficult. Recognizing the imaging features of no capsule, hypervascularity of the tumor including the fat component, and early venous drainage may be helpful for correctly diagnosing angiomyolipoma of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…However, no case of concurrent hepatocellular carcinoma and hepatic angiomyolipoma in TSC has been previously reported in the literature. It has even been reported that non-fatty hepatic lesions in TSC can be regarded as hepatic angimyolipomas [6,11] . In our patient, the imaging findings of multiple hepatic angiomyolpomas with fat component were in accordance with previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no case of concurrent hepatocellular carcinoma and hepatic angiomyolipoma in TSC has been previously reported in the literature. It has even been reported that non-fatty hepatic lesions in TSC can be regarded as hepatic angimyolipomas [6,11] . In our patient, the imaging findings of multiple hepatic angiomyolpomas with fat component were in accordance with previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…On dynamic contrast CT, it is often heterogeneous hyperdense in the arterial phase, hypodense with prominent central vessel in the portal venous phase. The enhancement pattern of hepatic angiomyolipoma is similar to that of hepatocellular carcinoma, so it's difficult to be differentiated from hepatocellular carcinoma [9][10][11] . However, no case of concurrent hepatocellular carcinoma and hepatic angiomyolipoma in TSC has been previously reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also noted the same enhancement mode. [18][19][20] Yang et al 21 found that tumours were inhomogeneously enhanced with enhanced MRI, and other studies have reported contrast enhancement in the arterial phase and slight hyperintensity or equal density in the portal venous phase, 22 as a result of abnormalities in the vascular wall and lack of an arteriovenous fistula. 2.…”
Section: Discussionmentioning
confidence: 99%
“…In den übrigen Fällen ist eine zuverlässige Dignitätsaussage weder durch die Bildgebung noch durch anamnestische oder klinische Daten möglich, zumal auch das HCC in bis zu 1/3 der Fälle Fettgewebsanteile aufweist. Die bioptische Klärung ist deswegen immer angezeigt (positive HMB-45-Reaktivität beim AML; [28,32]). …”
Section: Leberzelladenomunclassified